Selection of the Best Computer Laboratory Assistant Using AHP and Smart Methods - Ari Amir Alkodri; Supardi Supardi; Burham Isnanto; Kiswanto Kiswanto (JURNAL SISFOTEK GLOBAL, 2022)
Computer Laboratory Assistant, abbreviated as ASLAB, includes a Lab Assistant in a Computer Laboratory. ASLAB helps improve service performance in the Computer Laboratory, such as assisting Lecturers when teaching practicum at the Computer Laboratory and assisting in installing software on Student laptops so that the performance of Computer Laboratory services is always good. Problems The Head of the Computer Laboratory has difficulty assessing the comparison of ASLAB with other ASLABs to determine the best or not good performance. The calculation of the final value uses the mean value method so that all criteria are considered to be of equal importance, so we cannot know which criterion is more important. The research objective is to apply the AHP and SMART methods for selecting the best Computer Laboratory Assistant so that it can determine the criteria and ranking weights for the best Computer Laboratory Assistant so that it can be used as a basis for decision making and applied by the Head of the Computer Laboratory in selecting the best Computer Laboratory Assistant.